Forensic Systematic Fungal Infection Identification by PCR-DGGE in Human and Chicken Blood Samples - Mohammad J. Al-Jassani (Journal of Global Pharma Technology, 2018)
PCR can act as a key clue in court after fungus infection is determined that give an indication of the source of infection in order to determine either a zoonotic infection and/or a possible bio-terror action in a disease outbreak or poisoning bio-crime. Total of 30 blood samples were collected in the EDTA tube that include (10 healthy (asymptomatic) human blood samples, 10 chicken blood samples and 10 human blood of poultry workers. The PCR-DGGE analysis showed multi-banding pattern for some ‎samples, which means that they are infected with more than one fungal ‎species. Some of these bands (OUT) are shared between human (asymptomatic), Chicken and poultry workers. Periodic fungal infections follow up, using PCR-DGGE technique, for fungal population variation and ‎detection of any new emerging strain, are highly recommended.Keywords: Forensic, Fungal infection, PCR-DGGE.